Dental Radiology In Clinical Practice: Principles, Techniques, And Diagnostic Value (The Review of Diabetic Studies, 2024)
Modern dentistry uses dental radiography to make accurate diagnoses, plan treatments, and keep an eye on the health of the mouth and face. Modern imaging technology has greatly lowered radiation exposure while also making pictures clearer, diagnoses more accurate, and patient safety better. This review gives a full picture of dental radiology, from the basic principles of radiation physics to the main imaging techniques, radiation safety measures, clinical uses in different dental specialities, and new technologies like digital imaging and artificial intelligence. To achieve optimal patient outcomes and ensure evidence-based clinical decision-making, it is essential to understand the diagnostic efficacy of dental radiology.